2002
DOI: 10.1139/s02-008
|View full text |Cite
|
Sign up to set email alerts
|

Biologically induced clogging of a granular medium permeated with synthetic leachate

Abstract: The results of a laboratory column test conducted to gain insight regarding the clogging mechanisms within porous media are presented. Tests were conducted under saturated, anaerobic conditions using synthetic leachate that models Keele Valley Landfill (KVL) leachate in chemical compositions but has negligible suspended solids and bacterial concentrations compared with KVL leachate. Comparisons were made between tests conducted with synthetic leachate and similar column tests conducted with KVL leachate to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…Nevertheless, uncertainty regarding landfill bottom drainage layers formed from tire shreds remains a relevant issue. Fleming and Rowe [15][16][17] and Paksy et al [18] have researched the reasons for the clogging of the drainage layer with chemically and biologically mediated deposits. However, the process of how the clogging of biological and chemical origin takes place with waste materials in landfills still has not been properly investigated to have the right answer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, uncertainty regarding landfill bottom drainage layers formed from tire shreds remains a relevant issue. Fleming and Rowe [15][16][17] and Paksy et al [18] have researched the reasons for the clogging of the drainage layer with chemically and biologically mediated deposits. However, the process of how the clogging of biological and chemical origin takes place with waste materials in landfills still has not been properly investigated to have the right answer.…”
Section: Introductionmentioning
confidence: 99%
“…Since the abundance of microorganism in landfill leachate and inter-particle space of clay mineral in CCLs, the bio-clogging would occur (Rowe et al, 2000(Rowe et al, , 2002VanGulck et al, 2003). During the operation period of a landfill site, the bottom clay liners will be exposed to the leachate directly.…”
Section: Introductionmentioning
confidence: 99%
“…During the operation period of a landfill site, the bottom clay liners will be exposed to the leachate directly. The presence of biofilms and associated bio-clogging mechanisms controlled by the relative size of microorganisms can significantly reduce the hydraulic conductivity of the CCL (Rowe et al, 2000(Rowe et al, , 2002VanGulck et al, 2003). Additionally, as the bottom liner material, the clay should remain an excellent barrier performance in hydraulic behavior as well as its filtration performance.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the bulk mineralogy of the soil cover soils and clog matter collected in a landfill site, Bennett et al (2000) showed that a considerable portion of the clog material in LCS originated from soil daily covers. The significance of suspended solids on clog formation was highlighted by Rowe et al (2002). They conducted laboratory column tests with synthetic leachate (which contained negligible suspended organic and inorganic particles) and real leachate (which naturally contained considerable amount of these solids) to study possible clogging mechanisms of LCS.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, drainable porosity referred to the pore spaces that drain fluid freely in a gravitational field under atmospheric pressure. Rowe et al (2002) concluded that the physical clogging of suspended solids played a significant role in the clogging process, as the suspended solids provided abundant nucleation sites for further growth.…”
Section: Introductionmentioning
confidence: 99%